BOOK REVIEW: Marc Lynch, ‟The New Arab Wars: Uprisings and Anarchy in the Middle East”, New York: PublicAffairs, 2016 - GHILESCU, Anda (Studia Universitatis Babes-Bolyai Studia Europaea, 2018)
Marc Lynch’s latest book, The New Arab Wars: Uprisings and Anarchy in the Middle East, is a revitalizing take on the social and political transformations in the Middle Eastern region during and immediately after the Arab Spring. A professor of political science and international affairs at the George Washington University, Lynch has distinguished himself as a valuable voice on Middle Eastern studies, having previously published several books and articles on the topic and founding the Project on Middle East Political Science. This latest contribution to the field is not merely out of academic interest, but it is instead deeply rooted in the author’s perception of the crisis in Libya and the resulting NATO-led intervention in March 2011.